ECONOMIC FEASIBILITY STUDY BIOGAS POWER PLANT AT 80 TON/HOUR PALM OIL MILL - Mubarokah N Dewi (International Journal of Innovations in Engineering Research and Technology, 2021)
This research discusses the potential of organic liquid waste to generate power for palm oil mill processing. Currently the waste is used as fertilizer in a palm oil plantation. The waste releases methane into the atmosphere causing a greenhouse effect that can endanger the environment. On the other hand, methane contains potential as an energy source for electricity generation. This paper discusses the economic potential of this organic liquid waste from 80 ton/hour palm oil mill as a renewable energy. The analysis was carried out quantitatively in the form of total energy analysis and economic feasibility analysis of biogas utilization. Overall, this project is feasible to be executed based on the raw material supply and the electricity demand. With total investment about Rp. 57,9 billion and operational cost 2,7 billion rupiah/year, the company can make profit of up to 11 billion rupiah/year from selling the electricity, saving diesel fuel and saving shell. Total savings through diesel is around 1 billion rupiah/year. While the total sales of shell is about 1,2 billion rupiah/year. The economic analysis result is IRR 24,51%, payback period 4,68 year, NPV 62.995 billion.